Pengaruh financial technology dan literasi keuangan digital terhadap pengembangan UMKM di Fakultas Ekonomi dan Bisnis Universitas Sam Ratulangi Manado - Siampa, Felixius; Pontoh, Winston; Mawikere, Lidia M. (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to examine the influence of financial technology and digital financial literacy on the development of MSMEs at Sam Ratulangi University. This type of research is quantitative research using a descriptive approach. The sampling technique used was the random sampling method and produced 35 MSMEs as research samples from 50 MSMEs. By using data collection techniques using questionnaires. The data analysis technique in this study is multiple linear regression using the JAMOVI v2.23.28 program. The results of the study partially show that financial technology has a significant and negative effect on the development of MSMEs, digital financial literacy has a significant and positive effect and financial technology and digital financial literacy together have a significant and positive effect on the development of MSMEs at Sam Ratulangi University.